English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Find the derivative of each, Do not simplify

2006-10-18 04:44:30 · 4 answers · asked by Anonymous in Science & Mathematics Mathematics

4 answers

Its not really fair you just putting your homework questions on here, Allison.

See me after class.

2006-10-18 04:53:29 · answer #1 · answered by Stuart T 3 · 0 0

y = 2/(3x^3 + x)^5/2

= 2(3x^3 + x)^-5/2

Let (3x^3 + x) = t

dt/dx = 9x^2 + 1

y = 2t^-5/2

dy/dt = -5t^-7/2

therefore,

dy/dx = dy/dt*dt/dx

hence,

dy/dx = -5(3x^3 + x)^5/2^-7/2*(9x^2 + 1)

2006-10-18 05:54:44 · answer #2 · answered by Aazib A 1 · 0 0

y = 2/(3x^3 + x)^5/2

= 2(3x^3 + x)^-5/2

Let (3x^3 + x) = t

dt/dx = 9x^2 + 1

y = 2t^-5/2

dy/dt = -5t^-7/2

therefore,

dy/dx = dy/dt*dt/dx

hence,

dy/dx = -5(3x^3 + x)^5/2^-7/2*(9x^2 + 1)

2006-10-18 05:53:39 · answer #3 · answered by aazib_1 3 · 0 0

low d high minus high d low over low squared

2006-10-18 05:08:17 · answer #4 · answered by Helmut 7 · 0 0

fedest.com, questions and answers